Morpho-Syntactic Features of Mosuli Arabic Dialect - Sohaib Mahmood Khudhur (Journal of Daoist Studies, 2026)
Mosuli Arabic is a dialect of northern Iraq, primarily spoken in Mosul. It is still substantially underrepresented in current linguistic research, but it is important for morphosyntactic theories. This article is a detailed morphosyntactic study of Mosuli Arabic, focusing on verbal morphology and non-verbal clause structures. It deals with several phenomena: root and pattern morphology, aspectual distinctions, agreement, negation, and cliticization. It also deals with various nonverbal constructions, nominal, adjectival, locative, pronominal, and existential predicates, all of which have been extracted from data collected from local speakers. The research is theoretical in nature, based on a feature-based framework, where grammatical interpretation is based primarily on morphologically expressed features, rather than universally defined syntactic structures. The verbal complex of Mosuli Arabic provides rich grammatical information, which improves sentence economy. The dialect is characterized by verbless phrases and paratactic clause sequences. Conversations reveal interpretative and temporal relations rather than relying on syntactic markers. This means that meaning is conveyed through context and morphology, not through traditional grammar structures. These patterns challenge syntactic theories that depend heavily on projections and the universal availability of functional categories like tense phrases and obligatory copular structures. The results suggest that morphology and discourse can work together to bolster grammatical knowledge, reducing the need for massive syntactic projection. The work contributes to the field of Arabic dialectology with experimental methods and feeds into ongoing discussions about the relationship between morphology and syntax and the universality of functional categories.